Розвідки у Жовківському р-ні Львівської обл. - Назар, І.І. (Археологічні дослідження в Україні, 2010)
In 2009, expedition of the Scientific and Research Centre of the Rescue Archaeological Service of the IA NASU conducted the archaeological prospecting in Zhovkva Region of Lviv Oblast with the objective to uncover new sites and put them on the archaeological map of Lviv Oblast.